VD_FINDINFO Jug / 2025 / 444 vom 15. Januar 2025 - VD Tribunal cantonal (2025)
ABUS D'AUTORITÉ, REJET DE LA DEMANDE, FRAIS JUDICIAIRES, PRINCIPE DE L'ACCUSATION, DESSEIN | 312 CP, 34 CP, 42 al. 1 CP, 44 al. 1 CP